2010
DOI: 10.1371/journal.pone.0009706
|View full text |Cite
|
Sign up to set email alerts
|

GSK3 Influences Social Preference and Anxiety-Related Behaviors during Social Interaction in a Mouse Model of Fragile X Syndrome and Autism

Abstract: BackgroundNearly 1% of children in the United States exhibit autism spectrum disorders, but causes and treatments remain to be identified. Mice with deletion of the fragile X mental retardation 1 (Fmr1) gene are used to model autism because loss of Fmr1 gene function causes Fragile X Syndrome (FXS) and many people with FXS exhibit autistic-like behaviors. Glycogen synthase kinase-3 (GSK3) is hyperactive in brains of Fmr1 knockout mice, and inhibition of GSK3 by lithium administration ameliorates some behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
151
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(181 citation statements)
references
References 39 publications
26
151
1
Order By: Relevance
“…FMRP knockout mice show ALB (Mines et al 2010;Paz et al 2013;Tyzio et al 2014). The knockouts have a significant increase in global protein synthesis and in protein synthesis at the synapse (Bassell and Warren 2008).…”
Section: Genetics Of Epilepsy and Autismmentioning
confidence: 99%
“…FMRP knockout mice show ALB (Mines et al 2010;Paz et al 2013;Tyzio et al 2014). The knockouts have a significant increase in global protein synthesis and in protein synthesis at the synapse (Bassell and Warren 2008).…”
Section: Genetics Of Epilepsy and Autismmentioning
confidence: 99%
“…• lithium [113,122,123,134,[153][154][155] specific GSK3β antagonists [122,134] PAK Genetic (dn) Cellular: dendritic spine density (partially) [156] N/A N/A Shown are genetic and pharmacological rescue strategies and their effects in Fmr1 knockout mice. The following strategies were confirmed in studies using Drosophila models of fragile X syndrome (FXS): metabotropic glutamate receptor (mGluR) [167], gamma-aminobutyric acid (GABA) [168] (but see [169]), lithium [167], minocycline [170], phosphodiesterase-4 (PDE-4) [ A recent study suggested that simultaneous stimulation of D1R and serotonin (5HT) receptors rescued impaired synaptic AMPA receptor insertion and plasticity, and improved fear conditioning and Y maze learning deficits [115].…”
Section: Macro-orchidismmentioning
confidence: 99%
“…A major finding in brain samples of Fmr1 -/-mice is the abnormally high levels of GSK3b, a key kinase shown to play critical roles in several molecular pathways, including MAPK, Cyclin, Akt, and the canonical Wnt/b-catenin signaling pathway [26,[45][46][47]. The role of GSK3b, as part of the canonical Wnt/bcatenin signaling pathway, was shown to be important during adult neurogenesis in the murine hippocampus [29] and in FXS pathology in Fmr1 -/-mice [27,28].…”
Section: Expression Of Gsk3b and B-catenin In Fx-hnpcsmentioning
confidence: 99%